Listeria monocytogenes Contamination Characteristics in Two Ready-to-Eat Meat Plants From 2019 to 2020 in Shanghai - Zhang, Hongzhi; Wang, Jing; Chang, Zhaoyu; Liu, Xin; Chen, Weijie; Yu, Ying; Wang, Xiaoguang; Dong, Qingli; Ye, Yulong; Zhang, Xi (Frontiers in Microbiology, 2021)
Listeria monocytogenes is a ubiquitous foodborne pathogen that causes listeriosis, and is mostly linked to consumption of ready-to-eat (RTE) foods. Lack of hygiene in food processing environments may be a primary reason for contamination by L. monocytogenes isolates. In this study, L. monocytogenes strains isolated from two RTE meat processing plants in the Shanghai municipality, China, were characterized during 2019~2020 using pulsed-field gel electrophoresis (PFGE) and whole genome sequencing (WGS). Results showed that total 29 samples out of 239 (12.1%) were positive for L. monocytogenes, with eight (6.25%) and 21 (18.9%) isolates from plants A and B, respectively. The packaging room at plant A had the most contamination (14, 48.3%; P < 0.05), with a peak occurrence of 76.5% in processing environments. Nineteen L. monocytogenes isolates belonging to the pulsotype (PT) 7 group were indistinguishable (≥ 95.7%). Furthermore, core-genome multiple locus sequencing typing (cgMLST) identified up to nine allelic differences, and the closet pairwise differences among these ST5 isolates included 0~16 small nucleotide polymorphisms. Therefore, L. monocytogenes likely persisted at plant A during 2019 ~ 2020 with ongoing clone transmission. In contrast, no L. monocytogenes isolates were identified from processing environments at plant B. Most L. monocytogenes isolates were sampled from raw materials (62.5%). Several isolates (ST378, ST8 and ST120) were detected only once in 2020, and were considered as transient isolates. However, three ST121 isolates with the same PT (PT2) were detected in 2020, and should be noted for their stronger survival ability in harsh environments. These results suggest that continuous monitoring, stringent surveillance, and source tracking are crucial to guaranteeing food safety in RTE food plants.